The Significance of Extra-Cage Bridging Bone via Radiographic Lumbar Interbody Fusion Criterion. Issue 1 (January 2023) - Lee, Jeongik; Lee, Dong-Hoon; Jung, Chan-Woo; Song, Kwang-Sup
Study Design: Prospective observational study. Objectives: We aimed to analysis the distributional patterns of the intra- and extra-cage bridging bone (InCBB and ExCBB) and the significance of ExCBB using suggested lumbar interbody fusion criterion. Methods: This study included the patients with planned single-level transforaminal lumbar interbody fusion. We divided bridging bone into InCBB (in void of right or left cage) and ExCBB (outside of cages; anterior, posterior, intermediate, right, or left) and graded bridging scores from 0 to 2 on postoperative 1-year computed tomography. The fusion was defined as at least having one or more graded 2 and the evaluation were conducted twice by 2 raters. Results: Sixty-five patients were enrolled. All values of intra- and inter-rater reliability in left InCBB, anterior, and posterior ExCBB showed good agreements (≥0.75). Both InCBBs showed similar mean bridging scores (Rt:1.43 vs Lt:1.48), and in ExCBBs, the anterior was the highest (1.43), followed by the posterior (1.14); the right and left were the lowest (0.49 and 0.52 respectively). In subjects determined as fusion (85.4%), complete bridging was observed more in ExCBB (88.8%) than in InCBB (69.9%). Conclusions: Given the higher bridging scores in both InCBBs and Ant. ExCBB, bone grafting is important promoting factor to increase the interbody bridging bone regardless of outside or in void of cages. Based on our suggested criterion, ExCBB has a greater proportion compared to InCBBs for determining the fusion and extra-cage bone grafting should be considered as important procedures for interbody fusion.